Electron-Beam Pumped Semiconductor Lasers - Kawasaki, Brian (My University, 1972)
The major purpose of the work described in this thesis has been the development of an analytical model for the electron-beam pumped semiconductor laser system consistent with the main dynamic effects observed experimentally in the stimulated emission. The lasing mat4:!rials used in this study were single crystals of CdS, CdS1e and GaAs. The choice was made on the basis of the availability of high purity single crystals and for representation of both II-VI and III-V materials in the study.
Generally, the light output from a pulse-excited semiconductor laser changes in both wavelength and far-field pattern as a function of time during the excitation pulse. The effects investigated divide naturally into two parts. The first part deals with the tuning of the peak output of the stimulated emission toward lower energies during the excitation pulse. The second part deals with a deviation of the far-field radiation pattern of the spatial laser mode with respect to the cavity axis and the changes of this angle with time during the pump pulse.
In parallel with these investigations, a theoretical model of the semiconductor laser was developed. This model takes into account spatial variations in the gain and refractive index in the semiconductor material and changes in these profiles with time. The analysis, in terms of the experimental parameters, leads to a prediction of angular tuning of the far-field mode and can account for certain features of faster-than-bandgap wavelength tuning in a number of disparate laser materials. A particularly significant consequence of the model is the prediction of dramatic variations in cavity loss as a function of time. The major consequences of this effect for laser dynamics are discussed.
Keywords: Electron-beam; laser; semiconductor; stimulated emission